2022
DOI: 10.1002/jso.27094
|View full text |Cite
|
Sign up to set email alerts
|

Survival and failure modes of the Compress® spindle and expandable distal femur endoprosthesis among pediatric patients: A multi‐institutional study

Abstract: Background: Expandable endoprostheses can be used to equalize limb length for pediatric patients requiring reconstruction following large bony oncologic resections.Outcomes of the Compress ® Compliant Pre-Stress (CPS) spindle paired with an Orthopedic Salvage System expandable distal femur endoprosthesis have not been reported. Methods:We conducted a multi-institutional retrospective study of pediatric patients with distal femoral bone sarcomas reconstructed with the above endoprostheses. Statistical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In both cases, revision surgery was successful at obtaining osseous integration. The most common reason for revision was for infection which occurred in 6 of 36 patients at a mean time of 44 months 9 . This patient is nearly 3 years out from the index surgery without evidence of failure at the bone-implant junction, suggesting that this patient is outside the window of commonly seen osseous integration failure.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, revision surgery was successful at obtaining osseous integration. The most common reason for revision was for infection which occurred in 6 of 36 patients at a mean time of 44 months 9 . This patient is nearly 3 years out from the index surgery without evidence of failure at the bone-implant junction, suggesting that this patient is outside the window of commonly seen osseous integration failure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a long length of otherwise normal bone would be removed to implant an expandable prosthesis of appropriate lengthening potential. Prior studies have demonstrated that expandable prostheses have high failure rates ranging from 63% to 78%, typically requiring 2 additional surgeries unrelated to lengthening 8,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Endoprosthetic reconstruction can complicate options to correct limblength discrepancy because of the presence of implant stems and risk of prosthesis infection. Expandable prostheses exist but have high rates of reoperation and failure 1,[8][9][10] . In addition, sufficient bone must be removed for the expandable portion of the implant, creating additional challenges in patients with growth potential.…”
mentioning
confidence: 99%
“…The authors demonstrated lower mean implant survival time in patients who underwent high-dose radiation compared with patients who underwent no radiation. Tanaka et al performed a multi-institutional review of pediatric patients with distal femoral bone malignancies who underwent reconstruction with the Compress Compliant Pre-Stress spindle (Zimmer Biomet) paired with an Orthopedic Salvage System expandable distal femoral endoprostheses (Zimmer Biomet) 27 . The authors found high rates of osseointegration of the Compress spindle but high rates of failure of the expandable endoprosthetic device.…”
Section: Bone Tumorsmentioning
confidence: 99%